The acute effects of high-intensity interval training and moderate-intensity continuous exercise on declarative memory and inhibitory control. (September 2018) - Kao, Shih-Chun; Drollette, Eric S.; Ritondale, Joseph P.; Khan, Naiman; Hillman, Charles H.
Abstract: Objectives: To determine the effects of acute moderate-intensity continuous exercise (MICE) versus high-intensity interval training (HIIT) on two aspects of cognition: declarative memory and inhibitory control. Design: A within-subjects design. Methods: Thirty-six participants (female = 18, age = 21.5 ± 3.1 years) performed sessions of 20 min rest, MICE, and HIIT on separate days in counterbalanced order. Following each session, a free recall task and a modified flanker task were performed to assess declarative memory and inhibitory control. The P3 component of event-related brain potentials (ERPs) was measured during the flanker task to assess the neuroelectrical mechanism underlying inhibitory control. Results: Free recall performance was improved following MICE and HIIT compared to rest. During the flanker task, MICE and HIIT resulted in shorter reaction time compared to rest, and decreased reaction time interference scores were observed following HIIT compared to rest. Larger P3 amplitude was observed following MICE compared to HIIT and rest, whereas HIIT resulted in shorter P3 latency compared to rest. Conclusions: The present investigation demonstrated similar short-term facilitating effects on declarative memory and inhibitory control following MICE and HIIT, which may exert differential influences on neuroelectrical mechanisms underlying inhibitory control operations. Highlights: A single bout of exercise improves declarative memory and inhibitory control. Intense interval and continuous moderate exercise differentially affect cognition. High-intensity interval exercise may be a feasible means to enhance cognition.